Evaluation on men’s health knowledge: contribuitions for assistance in pratice technical level in nursing - Júlio César Santos da Silva, Suzy Darlen Dutra de Vasconcelos, Úrsula Pérsia Paulo dos Santos, Marcela dos Santos Ferreira, Maria José Coelho (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v4i3.4093